2017
DOI: 10.1128/jcm.02498-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of QuantiFERON-TB Gold-Plus in Health Care Workers in a Low-Incidence Setting

Abstract: Although launched in 2015, little is known about the accuracy of QuantiFERON-TB Gold-Plus (QFT-Plus) for diagnosis of latent M. tuberculosis infection (LTBI). Unlike its predecessor, QFT-Plus utilizes two antigen tubes to elicit an immune response from CD4 ϩ and CD8 ϩ T lymphocytes. We conducted a crosssectional study in low-risk health care workers (HCWs) at a single U.S. center to compare QFT-Plus to QuantiFERON-TB Gold in-tube (QFT). A total of 989 HCWs were tested with both QFT and QFT-Plus. Risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 26 publications
7
41
1
Order By: Relevance
“…Thus, the discrepancy between QFT-GIT and QFT-Plus might be affected not only by the differences in the antigenic stimulants (the absence of TB7.7 in the TB1 tube and addition of the TB2 tube) but also by the populations examined and the underlying conditions of the patients as well. However, as observed in previous IGRA studies (9,24,25,32), most of the discordant results (77.8%) were scattered within IFN-␥ levels of 0.30 to 1.00 IU/ml, which cross the assay cutoff ( Fig. 1).…”
Section: Qft-plus (Concn In Tb2 Minus Concn In Nil Tube)supporting
confidence: 79%
See 3 more Smart Citations
“…Thus, the discrepancy between QFT-GIT and QFT-Plus might be affected not only by the differences in the antigenic stimulants (the absence of TB7.7 in the TB1 tube and addition of the TB2 tube) but also by the populations examined and the underlying conditions of the patients as well. However, as observed in previous IGRA studies (9,24,25,32), most of the discordant results (77.8%) were scattered within IFN-␥ levels of 0.30 to 1.00 IU/ml, which cross the assay cutoff ( Fig. 1).…”
Section: Qft-plus (Concn In Tb2 Minus Concn In Nil Tube)supporting
confidence: 79%
“…Yi et al reported sensitivities of 98.6% and 97.6% for QFT-GIT and QFT-Plus, respectively, for the diagnosis of active tuberculosis in a Japanese population (26). In particular, the higher positivity rate with QFT-Plus in the study conducted by Moon et al was due to more frequent positive results with TB2 than TB1 (24). In this study, we observed a higher positivity rate with QFT-GIT (29.0%) than with QFT-Plus (27.8%), although we observed more TB1 Ϫ TB2 ϩ results with QFT-Plus.…”
Section: Qft-plus (Concn In Tb2 Minus Concn In Nil Tube)mentioning
confidence: 94%
See 2 more Smart Citations
“…The QFT-Plus assay was introduced on the IGRA market with the touted advantage of better sensitivity than its predecessor in immunocompromised hosts and after recent exposure. However, studies that have compared the QFT-Plus assay to the QFT assay have shown similar sensitivity in patients with active TB and similar test performance in HCW (1,5). As reported here, similarly to the implementation of the original QFT (3), we are seeing an increase in nonreproducible positive results in low-risk serially tested HCW (Fig.…”
supporting
confidence: 63%